Hakikat Pendidik Dalam Pendidikan Islam - Dilla Silvia; Heni Winda Siregar; Khairun Nisa Hasibuan; Mardinal Tarigan; Marzuki Marzuki (El-Mujtama: Jurnal Pengabdian Masyarakat, 2023)
Teachers in Islamic education are responsible for the development of students to reach their full potential. emotional, cognitive and psychomotor potential. teacher. Also refers to adults who are responsible for helping students develop physically and mentally to a level of maturity and competence. As a social being and as an independent being, only he is able to fulfill his duties as a servant of God. individual existence. Teachers should not only translate knowledge to students, but also teach students how to be good people. In this way, students will become good people with religious knowledge and beliefs. In Islamic education, students not only acquire intellectual wisdom but also emotional, social and spiritual. Keywords: educators, Islamic education